Minimization of exergy losses in a trapezoidal duct with turbulator, roughness and beveled corners. (25th August 2016) - Amirahmadi, S.; Rashidi, S.; Abolfazli Esfahani, J.
Highlights: For VG duct, total entropy generation decreases by creating the surface roughness. Friction exergy for VG duct increases locally near the vortex generator. The total entropy generation decreases by using beveled corners for duct. The friction exergy is higher for the VG duct especially at higher Reynolds number. The total exergy decreases by installing the vortex generators inside the duct. Abstract: This research is focused on the study of force convective heat and exergy transfers characteristics of flow through a trapezoidal duct with turbulator. Two vortex generators are located in the duct to enhance the heat transfer rate. The numerical simulations are done for the Reynolds numbers in the range of 400 < Re < 1600. The conservation of mass, momentum, and energy equations are solved numerically by applying a finite volume approach. The results are presented for the friction factor, Nusselt number, and entropy generations (Friction, thermal and total entropy generations). Finally, the attention is focused on the minimization of exergy losses by using two techniques. These techniques were use of beveled corners and surface roughness for the duct. It was found that the total entropy generation decreases by installing the vortex generators inside the duct. These reductions are 24.9%, 24.4%, 25.8%, and 26.6% for Re = 400, 800, 1200, and 1600, respectively. Moreover, the total entropy generation decreases by using beveled corners for duct. These reductions in the total entropy rates are in the vicinity of 10.4%, 9.15%, 8.54%, and 8.1% for Re = 400, 800, 1200, and 1600, respectively.